2010
DOI: 10.1002/ddr.20394
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes for enhanced cytotoxic activity of bleomycin

Abstract: The purpose of this study was to investigate the effect of liposome composition, which affects the nature of vesicular membrane on the cytotoxic efficacy of bleomycin. Formulation A comprised phosphatidylcholine (PC), cholesterol (CH), and dicetylphosphate (DCP). Formulation B employed PC, CH with dioleoylphosphatidylethanolamine (DOPE) as the fusogenic component. Formulation C consisted of rigid liposomes comprising dipalmitoylphosphatidylcholine (DPPC), CH, and DCP. Preparation D contained dioleoylphosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
3
5
0
Order By: Relevance
“…[23,24] As expected, encapsulation and loading efficiencies obtained were significantly higher than those previously reported. [25,26] High entrapment efficiency, proper stability, and sustained release behavior which were observed in this study confirmed that the preparation process of nanoparticles was optimal. These achievements are probably related to the liposome components and their correct amounts.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…[23,24] As expected, encapsulation and loading efficiencies obtained were significantly higher than those previously reported. [25,26] High entrapment efficiency, proper stability, and sustained release behavior which were observed in this study confirmed that the preparation process of nanoparticles was optimal. These achievements are probably related to the liposome components and their correct amounts.…”
Section: Discussionsupporting
confidence: 73%
“…Their size and shape are appropriate for use a carrier system for drug delivery because the optimum size to evade of phagocytes and penetrate to the tumor cells should be lower than 200 nm . As expected, encapsulation and loading efficiencies obtained were significantly higher than those previously reported …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that bleomycin is a drug with relatively low permeability and minimal intracellular concentrations. 7 , 8 Therefore, the rate-limiting step of the sclerosant effect of bleomycin lies in its membrane permeability. Alternative strategies have been investigated to enhance the permeability of drugs with low permeability through biological membranes.…”
Section: Introductionmentioning
confidence: 99%